2020
DOI: 10.35848/1882-0786/abbfdf
|View full text |Cite
|
Sign up to set email alerts
|

Chemically degraded grain boundaries in fine-grain Ba0.6K0.4Fe2As2 polycrystalline bulks

Abstract: In this study, we investigated nanostructure and local compositional variations at grain boundaries (GBs) in polycrystalline Ba0.6K0.4Fe2As2 (K-Ba122) bulks. Analytical scanning transmission electron microscopy revealed that K-Ba122 bulks made in a regular glove box filled with 99.9% Ar show Ba–O segregation at the GBs, forming a network of insulated GBs. By significantly reducing the oxygen and water content in the glove box, K became preferential segregation at GBs. Our nanostructural study suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The condition of synthesis of polycrystalline sample directly affects the sample quality [42,48]. Kametani et al reported that oxygen and water level should be significantly reduced in the synthesis environment [25]. Otherwise, insulating the Ba-O network is formed at the grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition of synthesis of polycrystalline sample directly affects the sample quality [42,48]. Kametani et al reported that oxygen and water level should be significantly reduced in the synthesis environment [25]. Otherwise, insulating the Ba-O network is formed at the grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…Superconducting wires and tapes fabricated by a powder-in-tube (PIT) method using polycrystalline (AE,K)Fe 2 As 2 powders have been also studied [17][18][19][20][21][22][23][24]. Transport J c of wires and tapes can be increased by purification of raw materials [25] and the densification of the core [26] to eliminate weak links between superconducting grains. To enhance J c by densification of the superconducting core, pressing at high temperature is effective for IBS wires.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen contamination, even at low levels, degrade GB connectivity in K-Ba122. 24,25,30) The highest J c of polycrystalline Ba122 reported to date is found in flat tape conductors. It is considered that such a high J c in the tapes is correlated to uniaxially textured Ba122 grains, [31][32][33][34][35][36][37] although the effects of uniaxial texture on J c across the GBs are not as simple as in [001]-tilt bicrystals due to more complex inter/intra-grain current paths rather than along the ab-planes.…”
mentioning
confidence: 95%
“…The number of current paths would be physically reduced by an extrinsic current blocker at the GBs, including FeAs, Ba oxide and/or nanocracks which are dependent on the synthesis and processing. 25,26,29,30,40) Concerning intrinsic current limiters, it appears highly plausible that J c across the GBs in Fe-based superconductors including Ba122 decays as a function of GB misorientation angle, 19,20) although it is still largely unknown how much reduction in J c actually occurs in the GBs of K-Ba122. Nevertheless, previous studies suggested that grain alignment such as uniaxial or concentric texturing is beneficial for raising J c , 36,39) presumably due to improvement of intrinsic GB connectivity by reducing GB misorientation.…”
mentioning
confidence: 99%
“…For practical applications, it is necessary to minimize the adverse effect of the weak-link at grain boundaries, which limits transport superconducting current [5]. For the past decade, research on polycrystalline K-doped Ba122 has been conducted and demonstrated the improvement of transport critical current density (J c ) of bulks [6,7], wires, and tapes [8,9]. Recently, a high J c of 1.1 × 10 5 A cm −2 at 4.2 K * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%